Exploring Al-Ghazali’s concept of education: A study of speech acts through English language lens - Zurriyati, Zurriyati; Perangin-angin, Alemina Br; Rahman, Fadhlur (Universitas Islam Negeri Banda Aceh, 2023)
The purpose of this study is to provide an in-depth analysis of the types, functions, and manner of speech acts utilised in al-Ghazali's notion on educational concept. The study employed a content analysis methodology, which entailed gathering data from a variety of sources, including Al-Ghazali's writings and scholarly articles related to his works. The findings of this study reveal that al-Ghazali's idea of education in is dominated by directive speech acts, followed by assertive acts and constative acts. The category of recommending acts makes up the vast majority of directive acts, whereas order acts are somewhat less common. Further, Al-Ghazali’s use of speech acts tends to emphasize a competitive function, followed by a collaborative one. Interestingly, neither convivial nor conflicting functions are presented in this study. The dominance of directive speech acts, highlight Al-Ghazali's preference for providing guidance and advice to his readers in a harmonious and respectful communication style. Furthermore, Al-Ghazali's use of speech acts can be classified primarily as literal and direct speech acts, with subsequent employment of indirect and non-literal forms.. These findings contribute to the teaching learning process including English language in applying speech act. Finally, this study highlights the significance of considering the types, functions, and manner of performing speech acts propose to teachers and students in English language teaching learning process.